Sosialisasi Pemanfaatan Media Sosial Sebagai Pengembangan UMKM Di Kota Blitar - Devi Istyalita; Pandu Dewa Dana; Ardian Christyanti; Mirza Andrian Syah; Gideon Setyo Budiwitjaksono (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2023)
This study aims to explain the importance of socializing the application of social media in the development of Micro, Small and Medium Enterprises (MSMEs) in Blitar City. Social media has become a very effective tool in building relationships with customers, marketing products and increasing business visibility. However, there are still many MSMEs in Blitar City that have not utilized the potential of social media optimally. Through outreach, MSMEs owners will be provided with a better understanding of social media and how to use it as an effective marketing tool. This outreach will involve training and increasing knowledge on relevant social media platforms, online marketing strategies, creating engaging content, and measuring and analyzing social media performance. It is hoped that by socializing the use of social media, MSMEs in Blitar City will be able to make better use of social media to promote their products and services, reach a wider audience, and increase their online presence. With the increase in online presence, it is hoped that there will be an increase in the overall turnover and growth of MSMEs in Blitar City.